Aldol‐type group‐transfer polymerization of silyl vinyl ethers using silyl perfluoroalkaneimides as nonmetal catalysts. Issue 16 (29th May 2013) - Moyori, Takaya; Hayashi, Terunari; Takasu, Akinori
ABSTRACT: We investigated the catalytic activity of bis(nonafluorobutanesulfonyl)imide (Nf2 NH), acting as a Brønsted acid, and its silylated imide, t ‐butyldimethylsilyl nonafluorobutanesulfonylimide (Nf2 NTBDMS), acting as a Lewis acid, for aldol‐type of group‐transfer polymerization (Aldol‐GTP) of silyl vinyl ethers. Aldol‐GTPs of t ‐butyldimethylsilyl vinyl ether (VOTBDMS) and triethylsilyl vinyl ether (VOTES) proceeded in dichloromethane at 0 °C with benzaldehyde as the initiator. Nf2 NH catalyzed the polymerization of VOTBDMS although the product poly(VOTBDMS) had a molecular weight of 2510, which was considerably smaller than that predicted by the ratio of the initial monomer to initiator concentrations, and the smaller molecular weight was a consequence of desilylation of VOTBDMS before the polymerization step. Conversely, when Nf2 NTBDMS was used as the catalyst, poly(VOTBDMS) with molecular weight >16, 000 was obtained. The Nf2 NTBDMS‐catalyzed polymerization was more rapid than polymerizations that used t ‐butyldimethylsilyl trifluoromethanesulfonylimide, t ‐butyldimethylsilyl hexafluorocycropropanesulfonylimide, or zinc bromide as the catalyst, even though the ratio of Nf2 NTBDMS to the monomer was the smallest used. With VOTES as the monomer, and Tf2 NTBDMS as the catalyst, a poly(VOTES) with a syndiotactic tendency (mm:mr:rr = 9:44:47) was produced. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3516–3522 Abstract : The catalytic activity of bis(nonafluorobutanesulfonyl)imide (Nf2 NH), acting as a Brønsted acid, and its silylated imide, t ‐butyldimethylsilyl nonafluorobutanesulfonylimide (Nf2 NTBDMS), acting as a Lewis acid, was investigated for aldol‐type group‐transfer polymerization (Aldol‐GTP) of silyl vinyl ethers. Aldol‐GTPs of t ‐butyldimethylsilyl vinyl ether (VOTBDMS) and triethylsilyl vinyl ether (VOTES) proceeded in dichloromethane at 0 °C with benzaldehyde as the initiator. When Nf2 NTBDMS was used as the catalyst, poly(VOTBDMS) with molecular weight >16, 000 was obtained. With VOTES as the monomer and Nf2 NTBDMS as the catalyst, a poly(VOTES) with a syndiotactic tendency (mm:mr:rr = 21:30:49) was produced.